A Review on Ã¢â‚¬Å“Formulation, Development and Evaluation of Amisulpride Once Daily TabletÃ¢â‚¬Â - Upadhyat1, H. Bishnoi1, S. Savita1, S. Shailesh1*, O.P. Mahatama2, N. (Recent Research in Science and Technology, 2011)
TheÃ‚Â objectiveÃ‚Â ofÃ‚Â theÃ‚Â presentÃ‚Â studyÃ‚Â wasÃ‚Â toÃ‚Â developÃ‚Â once-dailyÃ‚Â tabletÃ‚Â ofÃ‚Â Amisulpride,Ã‚Â aÃ‚Â second generationÃ‚Â antipsychotic,Ã‚Â aÃ‚Â substitutedÃ‚Â Benzamide.Ã‚Â The tablets were prepared by the wet granulation method.Ã‚Â MicrocrystallineÃ‚Â Cellulose,Ã‚Â HydroxyPropylmethyl celluloseÃ‚Â Ã‚Â (HPMC),Ã‚Â Talc,Ã‚Â Magnesium Stearate,Ã‚Â IsoÃ‚Â PropylÃ‚Â alcohol, Xanthan Gum, Kollidone Cross Pobidone, Aerosil, AvesilÃ‚Â 101, 112,Ã‚Â 102, SodiumÃ‚Â B i-car bonate,Ã‚Â PolyÃ‚Â vinylpyrollidoneÃ‚Â K-30,Ã‚Â CarbopolÃ‚Â withÃ‚Â varyingÃ‚Â excipientsÃ‚Â SixÃ‚Â bilayerÃ‚Â formulations AM1 Ã¢â‚¬â€œAM6 wereÃ‚Â prepared by compressingÃ‚Â both Instant Release ( IR) and Sustained Release ( SR)Ã‚Â granules.Ã‚Â The granules were evaluated for bulk density, tapped density, compressibility, and Hausner ratio and moisture content. The tablets AM1Ã¢â‚¬â€œ AM6 were evaluated. The granules showed satisfactory flow properties.Ã‚Â AllÃ‚Â theÃ‚Â tabletsÃ‚Â formulationsÃ‚Â showedÃ‚Â acceptableÃ‚Â PharmacotechnicalÃ‚Â propertiesÃ‚Â andÃ‚Â complied withinÃ‚Â specificationsÃ‚Â forÃ‚Â testedÃ‚Â parameters.Ã‚Â TheÃ‚Â resultsÃ‚Â ofÃ‚Â dissolutionÃ‚Â studiesÃ‚Â indicatedÃ‚Â thatÃ‚Â the formulationÃ‚Â Ã‚Â Ã‚Â AM1 ,Ã‚Â AM2Ã‚Â Ã‚Â andÃ‚Â AM3Ã‚Â Ã‚Â theÃ‚Â releaseÃ‚Â retardant use in combinationÃ‚Â of SRÃ‚Â partÃ‚Â &Ã‚Â IRÃ‚Â part, AM1 (80:20), AM2 (80:20)in combination of HPMC and poloxmerÃ‚Â 188 and AM3Ã‚Â Ã‚Â use is xanthane gum but processÃ‚Â notÃ‚Â fissileÃ‚Â andÃ‚Â dissolutionÃ‚Â wasÃ‚Â faster.Ã‚Â Formulation AM6 exhibited satisfactory drug release; amisulpride OD Bi- layer 400 mg tablets dissolved more than 90% in 24 hours.